Political science and its methods: a comparison among the programs of social sciences in colombia (2013)
Resolution 466 of 2007, issued by the Ministry of National Education, represents an unprecedented avatar institutionalization of political science in Colombia. However, although advances in defining the specific quality characteristics and development of